2022
DOI: 10.1126/scitranslmed.abo3445
|View full text |Cite
|
Sign up to set email alerts
|

Diet-derived metabolites and mucus link the gut microbiome to fever after cytotoxic cancer treatment

Abstract: Not all patients with cancer and severe neutropenia develop fever, and the fecal microbiome may play a role. In a single-center study of patients undergoing hematopoietic cell transplant ( n  = 119), the fecal microbiome was characterized at onset of severe neutropenia. A total of 63 patients (53%) developed a subsequent fever, and their fecal microbiome displayed increased relative abundances of Akkermansia muciniphila , a species of mucin-degrading bacteria ( … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Given that the majority of bloodstream infections identified from patients with febrile neutropenia arise from an intestinal origin, the authors recently asked if the composition of intestinal bacteria could be associated with development of fever in HCT patients when they become neutropenic 42 . We found that patients who later developed fever had increased relative abundances of Bacteroides and Akkermansia muciniphila in their fecal samples collected at onset of neutropenia.…”
Section: The Microbiome and Allohctmentioning
confidence: 90%
See 2 more Smart Citations
“…Given that the majority of bloodstream infections identified from patients with febrile neutropenia arise from an intestinal origin, the authors recently asked if the composition of intestinal bacteria could be associated with development of fever in HCT patients when they become neutropenic 42 . We found that patients who later developed fever had increased relative abundances of Bacteroides and Akkermansia muciniphila in their fecal samples collected at onset of neutropenia.…”
Section: The Microbiome and Allohctmentioning
confidence: 90%
“…41 An examination of the intestinal microbiome of patients undergoing alloHCT conditioning before development of neutropenic fever, as well as the microbiome of mice following either total body irradiation (TBI) or treatment with melphalan in the absence of antibiotic treatment, both demonstrated that HCT conditioning alone can markedly modulate the composition of intestinal bacteria. 42 Interestingly, murine experiments demonstrated that mice, similar to humans, consume less food after TBI, and that much of the effects of HCT on the microbiome can be recapitulated with a simple 50% reduction in oral food intake in unirradiated mice. 42 Hence, nutritional supplementation strategies represent an approach that could mediate meaningful benefits on the intestinal microbiome and in turn improve clinical outcomes.…”
Section: Sources Of Microbiome Disruption In Allohctmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Schwabkey and colleagues have linked mucus-degrading bacteria in the gut to increased fever. These bacteria thin the mucus layer in mice, potentially exposing the hosts to further bacterial infections [69].…”
Section: Vicious Cycle Of Malnutrition and Enteric Diseases 21 Prolon...mentioning
confidence: 99%
“…A primary contributor to neutropenic fever not caused by an infection in patients following cytotoxic cancer treatment may lie in the gut. A study published in Science Translational Medicine showed that patients treated by hematopoietic cell transplantation who developed neutropenic fever not caused by an infection had a significantly increased abundance of the species of the mucin‐degrading bacteria Akkermansia muciniphila 1 …”
mentioning
confidence: 99%